Sintesis dan Karakterisasi Nanopartikel Perak Berbasis AgNO3 dan Ekstrak Daun Lamtoro (Leucaena Leucocephala) Untuk Aktivitas Antibakteri - Ayu Rosyida Zam Zam; Amin, Nashrul; Redjeki, Sri (Jurnal Serambi Engineering, 2026)
This study aims to synthesize and characterize silver nanoparticles (AgNPs) based on silver nitrate (AgNO₃) using Leucaena leucocephala leaf extract as a natural bioreducing agent, and to determine the effects of AgNO₃ concentration and stirring time on their morphology, stability, and antibacterial activity. The synthesis was carried out using AgNO₃ concentrations of 1.5, 2.5, 3.5, 4.5, and 5.5 mM, with stirring times of 2, 3, and 4 hours at room temperature. UV-Vis analysis showed that a concentration of 5.5 mM and stirring time of 3 hours produced a maximum absorption peak at approximately 430 nm, indicating the successful formation of stable silver nanoparticles. SEM analysis revealed spherical-shaped AgNPs with particle sizes ranging from 50 to 100 nm. The antibacterial activity test against Staphylococcus aureus ATCC 25923 showed an inhibition zone of 11.67 mm at 100% concentration, categorized as strong antibacterial activity. Therefore, the combination of 5.5 mM AgNO₃ concentration and 3 hours of stirring time was determined to be the optimum condition for producing stable silver nanoparticles with high antibacterial potential.